# Solving a pair of simultaneous equations using the substitution method.

In this article I will show you how to solve a pair of simultaneous equations by substitution. Make sure you can solve linear equations before you go any further. Remember, when you are solving simultaneous equations you are after the values and x and y that satisfy both equations.

When you are asked to solve simultaneous equations by substitution normally y (or another letter) will be the subject of one of the equations. Therefore, all you need to do is substitute this equation into the other equation which will give you one equation involving x. If you simplify and solve this resulting equation you will be able to find the value of x. Once x is known, you can find the value of y by substituting x into either equation 1 or equation 2.

Let’s take a look at a couple of questions on solving simultaneous equations by substitution.

**Question 1**

Solve this pair of simultaneous equations using the substitution method.

4x – 3y = 9 (equation 1)

y = 10 - 3x (equation 2)

Since y is the subject of equation 2 you can substitute this equation into equation 1.

This gives:

4x – 3(10 – 3x) = 9

Now multiply out the brackets and simplify. Take care with the negative sign before your bracket.

4x -30 + 9x = 9

13x – 30 = 9

Now solve this linear equation to find the value of x.

13x = 39

x = 3

Now since x is found substitute this into equation 1 to find the value of y.

4x – 3y = 9

12 – 3y = 9

-3y = -3

y = 1

Let’s take a look at one more question on solving simultaneous equations by substitution.

**Question 2**

Solve this pair of simultaneous equations using the substitution method.

5x + 2y = 23 (equation 1)

y = 16 - 4x (equation 2)

Since y is the subject of equation 2 you can substitute this equation into equation 1.

This gives:

5x + 2(16-4x) = 23

Now multiply out the brackets and simplify. Take care with the negative sign before your bracket.

5x + 32 -8x = 23

-3x + 32 = 23

Now solve this linear equation to find the value of x.

-3x = -9

x = 3

Now since x is found substitute this into equation 2 to find the value of y.

y = 16 - 4x

y = 16 – 4 × 3

y = 4

So the solution are x = 3 and y = 4

For some extra help try these links out:

More help on solving by substitution.

Trickier questions on solving simultaneous equations by substitution.

## More by this Author

- 0
Finding the modal class from a grouped frequency table is actually quite easy to do. All you need to do is to look for the group that has the highest frequency. This is because the mode is the number that comes up the...

- 12
Find the nth term of a quadratic number sequence.

- 0
The surface area of a triangular prism can be found in the same way as any other type of prism. All you need to do is calculate the total area of all of the faces. A triangular prism has 5 faces, 3 being rectangular and...

## Comments

No comments yet.